Gender difference in left atrial appendage occlusion outcomes: Results from the Amplatzer™ Amulet™ Observational Study - De Caterina Alberto Ranieri; Nielsen-Kudsk Jens Erik; Schmidt Boris; Mazzone Patrizio; Fischer Sven; Lund Juha; Montorfano Matteo; Gage Ryan; Lam Simon Cheung Chi; Berti Sergio (Elsevier, 2022)
Background: Percutaneous LAAO represents an alternative for stroke prevention in patients not tolerating anticoagulation. While women are at higher risk of complications during percutaneous coronary or valvular interventions, the impact of gender on LAAO outcomes is not well characterized. The current study assessed potential gender-related differences in procedural and long-term outcomes following left atrial appendage occlusion (LAAO).
Methods: 1088 AF patients were enrolled in the prospective, multicenter, Amplatzer™ Amulet™ Observational Study and followed for 2 years with scheduled adverse event assessments. The prespecified primary outcome was ischemic stroke, systemic embolism or cardiovascular (CV) death at 2 years. We also compared the rate of procedural success, device-related thrombus (DRT) and major bleeding between genders.
Results: 702 men and 386 women underwent LAAO. Implant successwas high, and similar between men and women (98.9 vs 99.5%, p = 0.58). Similarly, no difference was observed in the primary outcome (12.0 vs 12.5%, p = 0.82). Compared to the CHA2DS2-VASc predicted rate, we observed a numerically greater absolute risk reduction of ischemic stroke in women (from 7.6 to 2.1%/year) than men (from 6.2 to 2.2%/year). DRT through 2 years was similar between groups (1.6%, p = 0.96). We found no significant gender difference in terms of periprocedural or long-term (7.1 vs 7.6%/year) major bleeding.
Conclusions: In this large group of patients undergoing LAAO using the Amplatzer™ Amulet™ device we found no significant gender difference in terms of procedural or long-term clinical outcomes. Similarly to oral anticoagulation, device-based LAA occlusion renders AF-related stroke risk similar in women and men.